Biomarkers of Aortopathy in Marfan Syndrome. Issue 2 (March 2020) - Iskandar, Zaid; Mordi, Ify; Lang, Chim C.; Huang, Jeffrey T. J.; Choy, Anna-Maria
Abstract : Marfan Syndrome (MFS) is an autosomal dominant, genetically inherited connective tissue disorder which primarily affects the cardiovascular system, but can also have systemic manifestations. First described in 1896, MFS has a prevalence of around 1/5000 in the general population. It is becoming increasingly common to see patients with MFS in a clinical setting due to the improved care of patients with adult congenital heart disease and general improvement in survival. Mortality, however, remains high largely due to the risk of aortic dissection as a result of the aortic root dilatation frequently seen in these patients. Contemporary management has therefore been focused on imaging-based surveillance to prevent these catastrophic events and intervene surgically in a timely manner. However, it is increasingly recognized that some patients do suffer aortic dissection below the expected threshold for surgical intervention. With this in mind, there has been interest in the role of biomarkers as an adjunct to imaging in the care of these patients. This article will provide an overview of the literature on potential biomarkers studied so far in MFS, as well as potential future directions.